2022
DOI: 10.3389/fpls.2022.988485
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche selection shapes the assembly and diversity of microbial communities in Casuarina equisetifolia L.

Abstract: The plant microbiome profoundly affects many aspects of host performance; however, the ecological processes by which plant hosts govern microbiome assembly, function, and dispersal remain largely unknown. Here, we investigated the bacterial and fungal communities in multiple compartment niches (bulk soil, rhizosphere soil, root endosphere, phylloplane, and leaf endosphere) of Casuarina equisetifolia L. at three developmental stages in Hainan Province, China. We found that microbiome assemblages along the soil–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Additionally, the unique fungal genera in this study were ranked as follows: rhizosphere soil > leaf > root > stem among different niches (Fig. 5B), attributed to the fact that the fungal communities in oilseed rape mainly originate from the soil and are sequentially ltered by the plant niches (Lin et al 2022). Besides, above-ground plant tissues of oilseed rape can harbor a diverse range of fungal taxa, as plant leaves release a wide range of volatile organic compounds that can in uence microbial colonization (Whipps et al 2008).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, the unique fungal genera in this study were ranked as follows: rhizosphere soil > leaf > root > stem among different niches (Fig. 5B), attributed to the fact that the fungal communities in oilseed rape mainly originate from the soil and are sequentially ltered by the plant niches (Lin et al 2022). Besides, above-ground plant tissues of oilseed rape can harbor a diverse range of fungal taxa, as plant leaves release a wide range of volatile organic compounds that can in uence microbial colonization (Whipps et al 2008).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, it can be inferred that these fungi may also derive from the surrounding environment. A previous study suggested that air, dust, and rainwater are the primary sources of the phylloplane fungal community (Lin et al 2022). Furthermore, symbiotic microorganisms can have bene cial, neutral, or detrimental impacts on plant growth (Li et al 2022c).…”
Section: Discussionmentioning
confidence: 99%
“…Among fungi, Ascomycota and Basidiomycota were the dominant phyla in the rhizosphere of T. chinensis , but their composition was also affected by salt stress [ 35 ]. In addition, the network relationships among microorganisms can also reflect the occupation of ecological niches by each OTU [ 38 ]. In our study, salt stress increased the positive correlation among OTUs of rhizosphere bacteria of T. chinensis , which was speculated to be the result of cooperative resistance to saline habitats among OTUs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to successfully colonize leaves, all bacteria need to overcome several hurdles, such that the taxa that finally reach the surface and endosphere of plant leaves have been filtered by several factors ( 5 , 6 ). First, to find their way onto or into the leaf, microbes must overcome physical hurdles such as low water availability ( 7 ) and regulated stomatal openings ( 8 ).…”
Section: Introductionmentioning
confidence: 99%